2000
DOI: 10.1007/s11746-000-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of stripped and nonstripped borage and evening primrose oils and their emulsions in water

Abstract: Oxidative stability of stripped and nonstripped borage and evening primrose oils and their emulsions in water was evaluated. The results indicated that column chromatographic techniques provide an effective means for stripping vegetable oils of their minor components. However, some minor components may be retained in the stripped oils. The minor components in borage and evening primrose oils significantly (P < 0.05) influenced their oxidative stability in the dark. In contrast, the behavior of endogenous antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
5
30
1
Order By: Relevance
“…These fatty acids profile and concentrations are near to that reported in previous studies by Eskin (2008) and Tasset-Cuevas et al (2013). Total unsaturated fatty acids (83.31%) were higher than total unsaturated fatty acids (57.67%) observed by El-Gengaihi et al (2004) but similar to that observed by Khan and Shahidi (2000).…”
Section: Discussionsupporting
confidence: 87%
“…These fatty acids profile and concentrations are near to that reported in previous studies by Eskin (2008) and Tasset-Cuevas et al (2013). Total unsaturated fatty acids (83.31%) were higher than total unsaturated fatty acids (57.67%) observed by El-Gengaihi et al (2004) but similar to that observed by Khan and Shahidi (2000).…”
Section: Discussionsupporting
confidence: 87%
“…Abuzaytoun and Shahidi 26 showed upward tendency for CD value of coldpressed hempseed oil and flaxseed oil upon heating. Khan and Shahidi 27 reported that CD value of cold-pressed borage oil reached a maximum value of 20.1 at 60 for 120 h and kept this value for 168 h. There was no direct comparison between our data with these mentioned literatures because of the differences of oils and analysis method used in these works. These literature indicated that these differences on CD values among the oils were associated with fatty acid composition especially unsaturated fatty acids.…”
Section: Thermal Treatment Oven Testcontrasting
confidence: 55%
“…A small amount of dtocopherol was detected in BO while EPO had a smaller amount of a-tocopherol. However, the higher peroxide values (PV) observed for the non-stripped oils and their emulsions during photooxidation were attributed to the presence of endogenous chlorophylls, known catalysts of photooxidation An earlier study by Khan and Shahidi [28] showed that carotenoids and chlorophylls were significantly (p ,0.05) higher in non-stripped EPO compared to non-stripped BO. However, the better oxidative stability of the non-stripped oils and emulsions was attributed to the presence of tocopherols and specific phospholipids.…”
Section: Stability Of Bo and Epomentioning
confidence: 99%